Их позвал горизонт: [об открытиях и судьбах географов и путешественников] / Ю. А. Сенкевич, А. В. Шумилов - Сенкевич Юрий Александрович (Мысль, 1987)
Экземпляры: ЧЗ (20181009) / Инвентарный номер: 19747 / Цена: 3.10 / Сис.шифр: 26.8 / Авт.знак: С31 / ГРНТИ: 39 / ББК: 26.8Г